WILLINGNESS TO PAY UNTUK PENGEMBANGAN FASILITAS AGROWISATA KECAMATAN BANDUNGAN KABUPATEN SEMARANG (Studi kasus di Setiya Aji Flower Farm) - Indah Susilowati; Ike Mardiana; Mukson Mukson (Faculty of Animal and Agricultural Science, Diponegoro University, 2020)
Semarang Regency has a great agro-tourism potential. Volcanic soil suitable for planting and cool temperatures support it to be a place of recreation. The study was conducted at Setiya Aji Flower Farm (SAFF), a chrysanthemum agro-tourism in Jetis village, Bandungan District, which is managed by farmer groups and local communities. The management is still very simple by utilizing the pre-harvest chrysanthemum flowers for tourism. SAFF was able to bring in 107,966 tourists during 2017, with an entrance ticket currently at Rp 7,500 generates substantial additional income for the people of Jetis village. Unfortunately, the number of tourists decreased until 65% to an average of 3,127 tourists per month in 2018. One of the causes of the reduction in tourist visits was the unpreparedness of the SAFF to face of competition with new tourist objects with similar themes around SAFF that were very well managed and continued growing. The purpose of this study was to estimate the willingness of visitors to pay for additional facilities at SAFF Bandungan, Semarang Regency. This study used the Contingency Assessment Method (CVM) to 110 visitors. The results showed that the majority of visitors are willing to pay for additional facilities at SAFF agrotourism. Willingness to pay (WTP) is estimated at level Rp 13,000. These results provide insights to the manager of SAFF to raise the entrance ticket by adding facilities at SAFF.